Improving Mathematical Literacy: Strengthening Students’ Learning Motivation through Fairy Tales with the Title “Petualangan Tiga Saudara Menyelamatkan Selendang Pusaka” - Rinova Cahyandari; Dewi Fitriana (Jurnal Pendidikan : Riset dan Konseptual, 2023)
Mathematics is one of the subjects that are considered difficult and unpleasant. Students have difficulty in understanding the material presented by the teacher. This problem is related to student learning motivation which needs more attention. The purpose of this study was to determine the effectiveness of fairy tales in increasing students' learning motivation. Fairy tales are activities that can be used to strengthen mathematical literacy. This study uses a type of pre-experimental research with the number of respondents being 20 students who study in 4th grade elementary school. Collecting data in this study using a learning motivation questionnaire. The analysis was carried out on the pre-test and post-test data. The results showed that students' learning motivation increased after being given mathematics learning through fairy tale innovation. In fairy tales there are mathematical literacy skills presented in the form of illustrated stories, and games that create a pleasant atmosphere in the learning process so that learning motivation can increase.